Local Wisdom-Based Market Game to Improve Kindergarten Children's Language Skills - Estri Meiyanti; Santoso; Mochammad Widjanarko (Journal of Psychology and Instruction, 2022)
The lack of children's language skills is influenced by the need for students' ability to socialize. It is because children spend more time playing mobile games. This study aims to develop and describe the design of a market game based on local wisdom in Rembang to improve children's language skills. This research method used the Research and Development (R&D) method using Borg and Gall with ten stages. The population in this study were all Kindergarten B children in Gugus Dewi Sartika Rembang. The samples in this study were Group B children at Nugraha Putra Kindergarten, Melati Kindergarten, and Nusa Indah Kindergarten, Totaling 50 Children. Data Collection Techniques Using Observations, Questionnaires, Interviews, and Documentation. While the data analysis technique uses Quantitative Descriptive Analysis, Requirements Test, and t-Test. The results showed that developing market games based on local wisdom was feasible and could improve the language skills of Kindergarten B Rembang children with a t-test of 21,189 and t table of 4.381 then, or 21.189> 4.381 while the NAin value was 71 in the Effective Category. This study concludes that the development of market games based on local wisdom is needed, feasible, and effective following the design of market games relevant to children's and teachers' needs.